PENGARUH PELAKSANAAN HOME CARE TERHADAP KEMANDIRIAN (ACTIVITY DAILY LIVING) PADA PENDERITA STROKE NON HEMORAGIK DI WILAYAH KERJA PUSKESMAS PARIAMAN - AULIA, FAJRI FEBRINI; AMELIATI, SRI; SARI, DELFIA MAITA (As-Shiha : JOURNAL OF MEDICAL RESEARCH, 2024)
A person who has a stroke cannot do their daily activities which causes them to become less independent and need help from others so that patients must get home care services to train their independence again. The purpose of the study was to determine the effect of implementing home care on independence (activity daily living) in non-hemorrhagic stroke patients in the Pariaman Health Center Work Area in 2024. This type of research is quantitative research with the research method being a pre-experimental method with a one group pretest-posttest design. This research was conducted in the Pariaman Health Center Work Area on March 18 to March 25, 2024. The population in this study was 39 people, while the sample taken was 16 people. The results of the study showed that there was an increase in independence in activity daily living after home care was given to stroke patients. The implementation of home care has an effect on independence (activity daily living) in non-hemorrhagic stroke patients in the Pariaman Health Center Work Area (p=value 0.000 < (α 0.05). In conclusion, the provision of home care by nurses has an effect on independence (activity daily living) in non-hemorrhagic stroke patients in the Pariaman Health Center Work Area in 2024.